Performance of Concrete Containing Partial Granite and Tiling Wastes as Fine Aggregate - Kherraf, Leila; Kherraf, Sihem; Hebhoub, Houria; Belachia, Mouloud (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of this paper is to study the properties of different compositions of concrete made by substituting sand made of crushed limestone, which is over-exploited in Algeria, by two types of sands produced by the recycling of double-layer tiling and granite waste, respectively, with different mass percentages of 0, 10, 20 and 30%.
Keywords: Tiling sand; granite sand; concrete; mechanical performance; durability